2016
DOI: 10.1016/j.vetimm.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage effector responses of horses are influenced by expression of CD154

Abstract: Reactive intermediates contribute to innate immunity by providing phagocytes with a mechanism of defense against bacteria, viruses and parasites. To better characterize the role of CD154 in the production of reactive intermediates, we cloned and expressed recombinant equine CD154 (reqCD154) in Chinese Hamster Ovary (CHO). In co-culture experiments, CHO cells ectopically expressing reqCD154 elicited superoxide production in monocyte-derived macrophages (MDM). Collectively, our results indicate that regulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…According to the consistent detection of bands of 38 and 18 kDa matching the predicted MW of membrane-bound and cleaved (soluble) equine CD154, respectively ( 20 , 22 ), the anti-human CD154 mAb 5C8 was considered specifically cross-reactive with equine CD154 and used in the following flow cytometry experiments.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the consistent detection of bands of 38 and 18 kDa matching the predicted MW of membrane-bound and cleaved (soluble) equine CD154, respectively ( 20 , 22 ), the anti-human CD154 mAb 5C8 was considered specifically cross-reactive with equine CD154 and used in the following flow cytometry experiments.…”
Section: Resultsmentioning
confidence: 99%
“…In mice and man, CD154 has been established as a marker of T helper cell (Th) activation by antigens ( 8 , 16 , 17 ). CD154 is a member of the type II transmembrane protein of the TNF superfamily ( 17 19 ) with a predicted MW of 28.7 kDa in horses [GenBank accession: AQM73588.1 ( 20 )]. In humans and mice, the predicted MW of CD154 is 29 kDa, but the actual MW of CD154 is usually 33 or 39 kDa due to post-translational modifications of the protein ( 17 , 19 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Kergosien and Rice (1998) found that a single low dose (but not higher doses) of tributyltin oxide resulted in enhanced macrophage secretory function and the respiratory burst in mice six days after intraperitoneal injection. Because the burst in a macrophage can take up to 24 h to detect (Sponseller et al 2016), the zebrafish RBA may not be sensitive enough to detect a macrophage respiratory burst after only 2.5 h of PMA treatment (instead primarily detecting neutrophil respiratory bursts). This interpretation is supported by the flow cytometry data in this study wherein it was observed that there were roughly 10-fold more neutrophils at 96 hpf as compared to macrophages (see Figure 5).…”
Section: Compounds With Developmental But No Observable Immunotoxicitymentioning
confidence: 99%